QOL-52. USE OF CANNABINOIDS IN THE PEDIATRIC CENTRAL NERVOUS SYSTEM TUMOR POPULATION. Issue 2 (22nd June 2018) - Dorris, Kathleen; Channell, Jessica; Hemenway, Molly; Baroffio, Angelina; Ellison, Michael; Brionse, Natalie; Griesinger, Andrea; Donson, Andrew; Madden, Jennifer; Van Essen, Colleen; Levy, Jean Mulcahy; Ambruso, Daniel; et al.
Abstract: BACKGROUND: Cannabinoids, including cannabidiol (CBD) and tetrahydrocannabinol (THC), are a class of compounds found in marijuana. Numerous studies in adults have examined cannabinoid use in management of cancer-related symptoms such as nausea, anorexia, and pain. Less is known about the use in the pediatric oncology population. Lay interest is also increasing in cannabinoid use as anticancer therapy for pediatric central nervous system (CNS) tumors. METHODS: A prospective observational study is underway at Children's Hospital Colorado to evaluate cannabinoids' impact on quality of life using PedsQL™ 4.0 modules of pediatric CNS tumor patients who self-medicate with cannabinoid products. Laboratory assessments of neutrophil function, T-cell activity and pharmacokinetics of CBD, THC and associated metabolites are in process. Diaries collect exploratory information on cannabinoid use patterns. RESULTS: To date, 26 patients (13:13; male:female) have been enrolled with a median age of 6.6 years (range, 3.3-17.3 years). The most common tumor type in enrolled patients was embryonal tumors (10/26); 8/26 patients had low-grade glioma/glioneuronal tumors and 6/26 had high-grade gliomas. Eleven patients initiated cannabinoids concurrent with upfront standard treatment regimens. Five patients completed 12 months of cannabinoid therapy on study; 12 patients are off study after <12 months of therapy. Nine patients continue on cannabinoid therapy and remain in follow up. New enrollment continues. Preliminary immune function analyses identified impaired neutrophil superoxide anion production but normal directed migration in patients taking cannabinoids. CONCLUSIONS: Families of children with various CNS tumors are pursuing cannabinoid therapy for both antitumor purposes and supportive care.